Tindak Pidana Peredaran Pemalsuan Obat Berdasarkan Undang-Undang Nomor 36 Tahun 2009 tentang Kesehatan - Sabrina Siahaan; Sonya Airini Batubara; Noel Yoga Panggabean (Mahesa Research Center, 2020)
The purpose of this research is to find out about the Regulations for the Crime of Drug Counterfeiting According to Law Number 36 Year 2009 concerning Health, How is the Responsibility for the Crime of Drug Counterfeiting According to the Criminal Code and Law Number 36 Year 2009 Regarding Health and Obstacles That Become BPOM's Obstacles in Handling Drug Counterfeiting Crime. Methods This type of research in writing this thesis uses normative juridical research. The data of this study are secondary data, the collection technique is aligned with the nature of the research. The nature of the research is normative legal research and research is analyzed qualitatively, meaning that the existing data is analyzed in depth, holistically and comprehensively. The conclusion of this research is that the regulation regarding the criminal act of drug counterfeiting in the Indonesian Criminal Code Article 386 Paragraph (1) is prohibited from selling, offering or delivering drugs known to be counterfeited, with a maximum imprisonment of 4 (four) years. Law Number 36 Year 2009 Concerning Health, namely Article 196, Article 197, Article 198, Article 199, Article 201. Law Number 36 Year 2009 Concerning Health, criminal responsibility lies with the individual or the person, the criminal responsibility is given to the form of a fine 3 ( three) times the penalty is imposed, as well as additional penalties in the form of administrative sanctions. The constraints faced are the intensity of supervision, lack of compliance with procedure requirements, limited human resources, limited laboratory testing equipment.